Government Program Payment for Crop Cost-Return Budgets - Kastens, Terry L.; Dumler, Troy J. (My University, 2006)
This publication provides estimated figures for producers to budget.
MF2236_2006_10
Keywords: MF2236; Economics; Crops; MF